2012
DOI: 10.3892/mmr.2012.1189
|View full text |Cite
|
Sign up to set email alerts
|

Core2 O-glycan-expressing prostate cancer cells are resistant to NK cell immunity

Abstract: Core2 β-1,6-N-acetylglucosaminyltransferase (C2GnT) forms an N-acetylglucosamine branch in the O-glycans (core2 O-glycans) of cell surface glycoproteins. We previously revealed that the expression of C2GnT is positively correlated with poor prognosis in prostate cancer patients. However, the detailed mechanisms underlying their poor prognosis remain unclear. In the current study, we report that the core2 O-glycans carried by the surface MUC1 glycoproteins of prostate cancer cells play an important role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 14 publications
1
40
1
Order By: Relevance
“…Our research group has already reported that GCNT1-expressing cancer cells can escape from host immune defense system [15,17]. In this immunological evading 12 mechanism, galectin-3 binding to core 2 branching O-glycans expressed on cancer cell surface is an critical step to interfere contact of host natural killer cells with cancer cells [15,17]. Endogenous galectin-3 expression has been found to correlate with the malignant potential of tumors [28,29,30] and PCa progression [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has already reported that GCNT1-expressing cancer cells can escape from host immune defense system [15,17]. In this immunological evading 12 mechanism, galectin-3 binding to core 2 branching O-glycans expressed on cancer cell surface is an critical step to interfere contact of host natural killer cells with cancer cells [15,17]. Endogenous galectin-3 expression has been found to correlate with the malignant potential of tumors [28,29,30] and PCa progression [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, GCNT1 expressing PCa cells formed poly-N-acetyllactosamine on cell surface [17]. The poly-N-acetyllactosamine is a ligand for galectins [21,22].…”
Section: Gcnt1-overexpressing Cells Formed Larger Tumors On Orthotopimentioning
confidence: 99%
See 1 more Smart Citation
“…At present, these novel immunosuppressive functions were demonstrated in bladder cancer (13,23) and prostate cancer (14). However, considering that the correlation of C2GnT expression with a high-metastatic phenotype was observed in several other types of cancers (4-7), it seems plausible that those cancer cells also use these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This minireview summarizes the newly identified immunosuppressive functions of core2 O-glycans against NK cell immunity with an emphasis on the most recent advances (13,14,23). At present, these novel immunosuppressive functions were demonstrated in bladder cancer (13,23) and prostate cancer (14).…”
Section: Discussionmentioning
confidence: 99%